Yorkshire General Hospital (A) - Thompson, Kenneth R., (SAGE Business Cases., 2020)
Yorkshire General Hospital is facing intense market competition from health care facilities nearby. New hospitals are being added in the regional area and other hospitals are improving their physical facilities. Yorkshire General Hospital is one unit of a major health care chain that also is experiencing some growing pains and does not have the resources necessary to improve its technology or physical plant. For example, it is not possible to upgrade Yorkshire General Hospital rooms from single to double occupancy. In addition, historical fundraising would not provide the inflow of funds needed to immediately support the improvements at the hospital. Yorkshire General Hospital needs to make some creative decisions to meet immediate challenges while it works toward longer range technology and physical plant upgrades. Most of the changes involve building an engaged workforce to become more customer focused.Yorkshire General Hospital (A) discusses challenges the hospital needs to address in order to remain a strong competitor in the market. Yorkshire General Hospital (B) will provide the course of action that the hospital decided to pursue. Note that all names, institutions, and locations are fictitious, but are based on actual organizations and situations.